Penghindaran Pajak Berganda Secara Unilateral Terhadap Pengenaan Pajak Penghasilan Capital Gains Dihubungkan Dengan Ketentuan dalam Perjanjian Penghindaran Pajak Berganda Secara Bilateral - Reza Saleh (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2018)
This paper entitled “ The Avoidance of Double Taxation as Unilateral From Capital Gains Tax related to the Rules of Bilateral Treaty on the Avoidance of Double Taxation and Prevention of Tax Evasion between Indonesia and other Countries” is written due to the increasing flows of international exchange and investment into and out of a country, including of capital goods which likely leads to capital gains. Every country’s tax law unilaterally includes several rules of the exemption of double taxation, inclusive those of the capital gains. However, the law varies in its definition of population, domicile and income resources that it may harm tax payers and a country. For the problem to be resolved, Indonesia has entered into a bilateral treaty on the taxation with several countries. The problems of this research are a, how the unilateral exemption of double taxation applies to the capital gains tax in Indonesia? And b, how the capital gains tax applies to the treaty on the double taxation exemption between Indonesia and other countries? The research uses a descriptive analysis method and normative juridical approach. Data gathering technique employs a library research intended to collect data for supporting the research. Results of research reveal that the words of the law and treaty on the exemption of double taxation between Indonesia and other countries, except with Singapore, clarify the capital gains but they do not account for the variety of profit or loss statement due to the changed exchange rates. Key word : Taxation, Unilateral, capital gain